Structural optimization and biological evaluation of ML364 based derivatives as USP2a inhibitors - Son, Youngchai; Su, Yang Ji; Shin, Sang Chul; Park Seo Kyoung; Kim, Yeojin; Park, Jinyoung; Yu, Jinha (Academic Press, 2024)
Ubiquitination is a representative post-translational modification that tags target proteins with ubiquitin to induce protein degradation or modify their functions. Deubiquitinating enzymes (DUBs) play a crucial role in reversing this process by removing ubiquitin from target proteins. Among them, USP2a has emerged as a promising target for cancer therapy due to its oncogenic properties in various cancer types, but its inhibitors have been limited. In this study, our aim was to optimize the structure of ML364, a USP2a inhibitor, and synthesize a series of its derivatives to develop potent USP2a inhibitors. Compound 8v emerged as a potential USP2a inhibitor with lower cytotoxicity compared to ML364. Cellular assays demonstrated that compound 8v effectively reduced the levels of USP2a substrates and attenuated cancer cell growth. We confirmed its direct interaction with the catalytic domain of USP2a and its selective inhibitory activity against USP2a over other USP subfamily proteins (USP7, 8, or 15). In conclusion, compound 8v has been identified as a potent USP2a inhibitor with substantial potential for cancer therapy.